ADVANCES IN GUAVA PROPAGATION - Pereira, Fernando Mendes [UNESP]; Usman, Muhammad; Mayer, Newton Alex; Nachtigal, Jair Costa; Maphanga, Oscar Ranny Mbongeni; Willemse, Salomie (Soc Brasileira Fruticultura, 2017)
Guava (Psidium guajava L.) can be propagated by seed, layering, air layering, grafting (budding or grafting), cuttings (root or shoot) or tissue culture. Propagation by seed is used for rootstock production and for raising populations for screening at early phases in the breeding programs. Vegetative propagation methods are used to clone selected genotypes from these programs and commercial orchards because it perpetuates all characteristics of each cultivar. This review addresses different methods that can be used to propagate guava, the methods commercially adopted and the progress obtained in recent years. There are several propagation technologies available, however, the adoption levels are rather different between producing countries. Needs for improvement on the production of guava trees will be discussed.
Keywords: Psidium guajava; seeds; grafting; cutting; air layering; tissue culture